Selective modulation of visual sensitivity during fixation - Scholes, Chris D.; McGraw, Paul V.; Roach, Neil W. (American Physiological Society, 2018)
During periods of steady fixation, we make small amplitude ocular movements, termed microsaccades, at a rate of 1-2 every second. Early studies provided evidence that visual sensitivity is reduced during microsaccades - akin to the well-established suppression associated with larger saccades. However, the results of more recent work suggest that microsaccades may alter retinal input in a manner that enhances visual sensitivity to some stimuli. Here, we parametrically varied the spatial frequency of a stimulus during a detection task and tracked contrast sensitivity as a function of time relative to microsaccades. Our data reveal two distinct modulations of sensitivity: suppression during the eye movement itself, and facilitation after the eye has stopped moving. The magnitude of suppression and facilitation of visual sensitivity is related to the spatial content of the stimulus: suppression is greatest for low spatial frequencies while sensitivity is enhanced most for stimuli of 1-2 c/deg, spatial frequencies at which we are already most sensitive in the absence of eye movements. We present a model where the tuning of suppression and facilitation is explained by delayed lateral inhibition between spatial frequency channels. Our data show that eye movements actively modulate visual sensitivity even during fixation: the detectability of images at different spatial scales can be increased or decreased depending on when the image occurs relative to a microsaccade.